2007
DOI: 10.1086/518235
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional Magnetohydrodynamic Simulations of Cold Fronts in Magnetically Turbulent ICM

Abstract: Steep gradients of temperature and density, called cold fronts, are observed by Chandra in a leading edge of subclusters moving through the intracluster medium (ICM). The presence of cold fronts indicates that thermal conduction across the front is suppressed by magnetic fields. We carried out three-dimensional magnetohydrodynamic (MHD) simulations including anisotropic thermal conduction of a subcluster moving through a magnetically turbulent ICM. We found that turbulent magnetic fields are stretched and ampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 25 publications
6
72
1
Order By: Relevance
“…We note that implicit anisotropic heat conduction is non-monotonic (Sharma & Hammett 2007). This non-monotonicity did not crash the simulations based on the modified Lax-Wendroff scheme applied to solar flares (e.g., Yokoyama & Shibata 2001) and cold fronts in cluster of galaxies (Asai et al 2004(Asai et al , 2005(Asai et al , 2007. We confirmed that our HLLD code combined with the implicit solver for the heat conduction reproduces the results of three-dimensional MHD simulations with heat conduction reported by Asai et al (2005).…”
Section: Methodssupporting
confidence: 78%
See 3 more Smart Citations
“…We note that implicit anisotropic heat conduction is non-monotonic (Sharma & Hammett 2007). This non-monotonicity did not crash the simulations based on the modified Lax-Wendroff scheme applied to solar flares (e.g., Yokoyama & Shibata 2001) and cold fronts in cluster of galaxies (Asai et al 2004(Asai et al , 2005(Asai et al , 2007. We confirmed that our HLLD code combined with the implicit solver for the heat conduction reproduces the results of three-dimensional MHD simulations with heat conduction reported by Asai et al (2005).…”
Section: Methodssupporting
confidence: 78%
“…Without it, the sharp temperature discontinuity quickly disappears because the subcluster plasma is heated by the hot ambient plasma, as mentioned by Ettori & Fabian (2000). Asai et al (2004Asai et al ( , 2005Asai et al ( , 2007 also confirmed the suggestion by Vikhlinin et al (2001aVikhlinin et al ( , 2001b) that the magnetic fields stretched and strengthened along the front suppress the growth of the Kelvin-Helmholtz (K-H) instability at the interface between the subcluster plasma and the ambient plasma.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Magnetic fields may also play significant roles in the dynamics and thermal conduction properties of "cold fronts", which are contact discontinuities separating merging subclusters (e.g., Vikhlinin et al 2001;Asai et al 2007;Dursi & Pfrommer 2008). That is a similar physics problem in some respects, although strong differences in the initial conditions, relative properties of the media, and the overall dynamics make direct comparisons between magnetic field roles in cold fronts and bubble boundaries nontrivial.…”
Section: Introductionmentioning
confidence: 99%